Students' Perception of the Implementation of Online Learning on Air Conditioning Engineering Course - Aulia, Irham; Rohendi, Dedi; Berman, Ega Taqwali; Wiyono, Apri (Journal of Mechanical Engineering Education, 2020)
The purpose of this study was to find out how students’ perceptions of online learning in terms of learning facilities, the ability of lecturer and students, as well as their learning activities. This research uses descriptive quantitative method. The data collection technique used in this research is a closed questionnaire filled out by Competency-Based Curriculum Refrigeration and Air Conditioning Engineering, Department of Mechanical Engineering Education, Universitas Pendidikan Indonesia students who contracted the Air Conditioning Engineering course, the sample was the entire population of the study. The results of this study indicate that students have good online learning facilities, students and lecturer can use learning facilities properly, and online learning activites are also carried out well. However, the results of the study also showed that the majority of students stated that online learning was not easier to understand and was not more interesting when compared to conventional learning.